OTT applications driving data revenue growth - Stephen Esselaar; Christoph Stork (International Telecommunications Society (ITS), 2018)
This paper analyses the impact of Over the Top applications (OTTs) on mobile operator revenues. Operators have argued that OTTs have cannibalised voice and SMS revenues and warned that the resulting decline of overall revenues leads to lower investment in network infrastructure; substandard quality of service; lower tax revenues and lower licensing revenues. This paper investigates this claim by using publicly available information from mobile operators across Africa to analyse trends in voice, SMS and data revenues. The paper analyses three factors impacting revenue trends: changes in usage pattern across voice, SMS and data, the impact of regulatory interventions and choice of business model. The paper shows that most operators across Africa have experienced strong revenue growth due to an OTTinduced increase in data revenues that outpaces potential decreases in voice and SMS revenues. Only a few operators saw a decline in service revenues over the last five years. Factors explaining the decline include regulatory interventions, economic decline of a country (drop in GDP), and being stuck in a voice and SMS centred 2G business model. Operating a mostly 2G network makes an operator vulnerable to losses in international and domestic call and SMS revenues while at the same time not being able to generate more data revenues. Case studies of Liberia, Guinea, Nigeria and Ghana are used to illustrate the impact of a decline in GDP and subscriber numbers, foreign exchange and competition, the impact of regulatory interventions and a data-centric business model. The paper argues that policy makers and regulators should be more concerned with stimulating network investment into 4G+ and less with attempting to protect operators from the impact
Keywords: 330